Utilization of 3D visual effect crossing facility to enhance pedestrian safety - Gen, N L; Ambak, K; Othman, M H; Yazid, M R M (2020)
Pedestrian is known as vulnerable road user, therefore proper crossing facility is needed to enhance the pedestrians’ safety. This study is to determine the effect of using 3D visual crossing facility inside the campus and its functionality. This 3D visual effect crossing facility is installed at selected location. The location selection is based on the absence of crossing facility, pedestrian volume and spot speed study. Pedestrian volume was collected by manually while spot speed study was collected using speed gun Apps. The 3D visual effect road crossing then is designed by using the perspective view from the driver height sight. After the installation of road crossing, the hypothesis is tested using chi-square analysis to determine the association between the effect on 85th percentile speed, pedestrians’ behaviour and the 3D visual effect crossing facility. The results of chi-square analysis shows there is a significant (p<0.05) association between speed of vehicles and the installation of 3D visual crossing facility. The results of the analysis revealed that before the installation, the percentage of motorists slow down is 39.7% while the motorists that do not slow down is 66.7%. After 1 week installation, the drivers that do not slow down the speed decrease from 59.52% to 40.48%. As a result, the effect of 3D visual crossing facility shows that the motorists will slow down their vehicle speed, immediately after the installation. However, after familiar with the presence of this facility some motorists are driving as usual without concern to anymore.